Primary Effusion Lymphoma without an Effusion: A Rare Case of Solid Extracavitary Variant of Primary Effusion Lymphoma in an HIV-Positive Patient - Hamza Hashmi; Drew Murray; Samer Al-Quran; William Tse (Case Reports in Hematology)
Primary effusion lymphoma (PEL) is a unique form of non-Hodgkin lymphoma, usually seen in severely immunocompromised, HIV-positive patients. PEL is related to human herpesvirus-8 (HHV-8) infection, and it usually presents as a lymphomatous body cavity effusion in the absence of a solid tumor mass. There have been very few case reports of HIV-positive patients with HHV-8-positive solid tissue lymphomas not associated with an effusion (a solid variant of PEL). In the absence of effusion, establishing an accurate diagnosis can be challenging, and a careful review of morphology, immunophenotype, and presence of HHV-8 is necessary to differentiate from other subtypes of non-Hodgkin lymphoma. Treatment involves intensive chemotherapy, and prognosis is usually poor. We present a rare case of a PEL variant in an HIV-positive patient who presented with extensive lymphadenopathy without any associated effusions.